Ethnobotany of the Malay Community in East Lingga Sub-District, Lingga District, Riau Island - Sujiah Putri, Ajeng; Zuhud, Ervizal A.M.; Siswoyo (Media Konservasi, 2024)
The Malay ethnic community in the Lingga Timur District is one example of how dependence on natural resources, particularly plants, has long existed to support human requirements. This is according to the field of ethnobotany. This study intends to identify the plants used and how the community in the East Lingga District uses plants based on local knowledge. The data were then descriptively and qualitatively assessed after being gathered through field observations and interviews with 71 respondents. There are 366 plant species from 103 known plant families found in East Lingga. Most of the families discovered belonged to the Fabaceae, including food, fuel, building supplies, ropes and crafts, medicinal plants, and other resources. Most sources for procurement are from the wild (58%), with 176 tree species, trees are the most common plant habitus. Leaves are the most frequently used plant component.